Is it safe to perform an anastomosis for rectal cancer after prostate cancer? A multicentre study of 126 patients from the GRECCAR group. (28th January 2022) - Lakkis, Zaher; Doussot, Alexandre; Manfredelli, Simone; Vernerey, Dewi; Meillat, Hélène; Ouaissi, Mehdi; Cotte, Eddy; Faucheron, Jean‐Luc; Piessen, Guillaume; Tuech, Jean‐Jacques; Lefevre, Jérémie H.; Panis, Yves; et al.
Abstract: Aim: To determine the safety of performing an anastomosis after rectal cancer (RC) resection in patients with a previously treated prostate cancer (PC). Methods: Patients with a previously treated PC who underwent rectal resection from 2008 to 2018 were retrospectively included. Outcomes were compared between patients who underwent rectal resection with anastomosis (restorative surgery, RS+ group) and those with a definitive stoma (RS− group). In the RS+ group, anastomotic leak (AL) rates were assessed according to the type of reconstruction. Results: A total of 126 patients underwent rectal surgery for mid‐low RC after a previous PC treated by radiotherapy (RT) and/or radical prostatectomy. Overall, 80 patients (63%) underwent a RS and 46 patients (37%) underwent rectal surgery with a definitive stoma. There was no statistical difference between the two groups in terms of intraoperative data, except for the type of resection with more multivisceral resection in the RS‐ group ( p < 0.01). In the RS+group, a diverting stoma was performed in 74% of cases. No difference between the two groups in terms of overall morbidity was found. In the RS+group ( n = 80), 17 patients (21%) experienced AL. Of these, none was observed when delayed coloanal anastomosis was performed ( p = 0.16). Long‐term permanent stoma in the RS+ group was 16% ( n = 13). Conclusion: Restorative surgery after resection for RC in patients with a previous history of RT and/or radical prostatectomy for PC is safe without additional morbidity. In selected patients for restorative surgery, performing delayed coloanal anastomosis may represent a promising option.